The Influence of Shopping Experience, Brand Prestige, and Perceived Value Toward The Loyalty of Transmart’s Visitors - Zahrina Nadine; R.R. Ratna Roostika (Syntax Literate, 2022)
The purpose of this research is to explore the effectiveness of education experience, entertainment experience, esthetics experience, escapist experience, brand prestige, and perceived value on Transmart visitors’ loyalty in Indonesia. The population of this study was comprised of customers who visited Transmart. Several Transmart branches located in big cities in Indonesia were chosen for the survey, including Yogyakarta, Semarang, Surabaya, Bandung, and Jakarta. The survey was carried out over a nine-week period from January to March 2022. The information was obtained through the use of an online survey constructed with Google Forms which was filled out by 250 respondents. The data used in this study were statistically analyzed using SmartPLS and AMOS 22. According to the study's findings, the education experience, entertainment experience, esthetics experience, and escapist experience have a positive effect on brand prestige for Transmart visitors in Indonesia. Secondly, brand prestige even has a positive effect on Transmart visitors' perceived value, and perceived value has a positive effect on Transmart visitor loyalty.